AB0276 The MRI Features in Patients with Rheumatoid Arthritis RA in Clinical Remission or Low Disease Activity. (10th June 2014) - Bensaoud, N.; Rostom, S.; Bahiri, R.; Amine, B.; Allali, F.; Hajjaj-Hassouni, N.
Abstract : Objectives: To evaluate in patients with RA in clinical remission or low disease activity (LDA), the synovitis and the osteitis using MRI by OMERACT RAMRIS score (RAMRIS bone edema and synovitis RAMRIS). Methods: In this longitudinal study, were included patients with rheumatoid arthritis RA according to the American College of Rheumatology ACR 1987 criteria with inadequate response or intolerance to DMARDs, treated with tocilizumab (TCZ).Sociodemographic characteristics, clinical and laboratory for the disease were collected at baseline (M0) and 06 months (M6) of treatment. Clinical remission was defined by a DAS28-CRP <2.6. The low disease activity (LDA) was defined by DAS28-CRP ≤2.6 <3.2. All patients underwent MRI of the dominant hand and wrist. MRI features were evaluated according to the Outcome Measure Clinical Trial in Rheumatoid Arthritis Rheumatoid Arthritis MRI Scoring system (OMERACT RAMRIS synovitis and bone oedema). Results: 22 patients with RA were included, 19 females (86.4%), with a mean of age 42±13.7. The mean disease duration was 8±5.2 years.The mean DAS28 was 5.8±0.94. Three patients were excluded from the study for serious side effects. At 06 months, 13 patients (52%) were in clinical remission, 04 patients (16%) in LDA, and 04 patients (16%) had active disease. The mean SDAI was 21.5±19.7.The mean CDAI was 16±19.6.The mean RAMRIS score was 2.23±6.33 for bone oedema, 4.76±4.02 for synovitis and 43.32±30 for erosion.Using DAS28CRP as criteria of remission, it did not exist significant differences between the 3 groups of patients (remission/LDA/active disease) for the presence of synovitis on MRI (p=0.67), and their severity (RAMRIS synovitis p=0.50). There was also no difference between the three groups for the presence of bone oedema (p=0.55), and their severity by RAMRIS bone oedema (p=0.55). Moreover, defining remission by SDAI and CDAI, the RAMRIS synovitis and bone oedema RAMRIS did not differ by the level of disease activity. Thus synovitis and oedema bone are not frequent in patients in clinical remission (synovitis/osteitis: 69%/75%) versus (15.4%/25%) LDA. Conclusions: This study suggests that patients in clinical remission or LDA evaluated by DAS28CRP showed no inflammation (synovitis and bone edema) on MRI. Although MRI and ultrasound are currently one of the criteria for remission in RA, further studies are needed in particular to determine the threshold definition of remission on MRI Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5959